Electromagnetic Loss Modeling and Demagnetization Analysis for High Speed Permanent Magnet Machine - Zhang, Yue; McLoone, Sean; Cao, Wenping (IEEE transactions on magnetics, 2018)
This paper presents a research work on the electromagnetic loss modeling and demagnetization analysis for a high-speed permanent magnet machine (HSPMM). The iron loss is estimated by improved modeling considering harmonics and rotational magnetic field effects to achieve high precision; rotor eddy current loss is researched and comprehensively investigated using finite-element method (FEM). The auxiliary slot and PM beveling are also proposed to reduce the rotor eddy current loss for machine at high-speed operation. Temperature-dependent PM demagnetization modeling is utilized in HSPMM FEM analysis to investigate machine performance due to temperature variation, while optimized rotor structures are proposed and comparatively researched by FEM to improve the machine anti-demagnetization capability in harsh conditions. The HSPMM temperature is estimated based on the calculated loss results and machine computational fluid dynamic modeling. Experimental measurements on the prototype machine verify the effectiveness of the machine electromagnetic and thermal modeling in the paper.